Profile of Antiviral and Antibiotic Prescribing in COVID-19 Patients in Bengkulu Indonesia - Muslim, Zamharira; Deby, Kadek; Candrawati, Helena Julia; Jatiningsih, Setiyati (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2024)
Coronavirus Disease 2019 (COVID-19 ) is caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus and has a fast spread rate. The treatment for COVID-19 was at the beginning of the pandemic, and until now, it cannot be determined with certainty, so various efforts have been made. Treatment can be in the form of antiviral therapy until the use of antibiotics given at the start of the pandemic. The aim of this study is to identify antiviral and antibiotic use patterns in COVID-19 patients at a government hospital in Bengkulu City, Indonesia. This research was conducted by retrospective collection using secondary data (Medical Records) of COVID-19 patients hospitalized at a Regional General Hospital (RSUD) Dr M. Yunus Bengkulu from June to September 2021. In this study, a sample of 232 patient medical records was obtained. Common symptoms in confirmed COVID-19 patients were weakness (76.29%), cough (67.67%), shortness of breath (65.52%), flu (43.10%), fever (42.24%), etc. In this study, the most comorbid disease was hypertension (10.34%). There are three types of antiviral prescribed for COVID-19 patients: Favipiravir (49.56%), Remdesivir (19.82%), and Oseltamivir (15.51%), but 15.08% of patients were not prescribed antivirals. The prescription of antibiotics in this study varied, Azithromycin (53.02%), Ceftriaxone (24.57%), Cefixime (18.53%), and several other types of antibiotics, while 9.91% of patients were not given antibiotics. Antiviral therapy for COVID-19 patients was Favipiravir, Remdesivir, and Oseltamivir. Favipiravir is the most widely used antiviral drug. Meanwhile, the most widely used antibiotic therapy for COVID-19 patients is Azithromycin.